1987
DOI: 10.1161/01.cir.75.4.877
|View full text |Cite
|
Sign up to set email alerts
|

Results of sympathetic denervation in the canine heart: supersensitivity that may be arrhythmogenic.

Abstract: Latex-induced transmural myocardial infarction or epicardial application of phenol interrupts sympathetic fibers innervating myocardium apical to the infarction or to the phenol-painted area. These denervated regions subsequently show supersensitive shortening of effective refractory period (ERP) in response to the infusion of norepinephrine (denervation supersensitivity). The purpose of this study was to test the hypothesis that such denervation supersensitivity is arrhythmogenic. Ventricular arrhythmias were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(96 citation statements)
references
References 29 publications
3
92
0
1
Order By: Relevance
“…It can result in "denervation supersensitivity" to circulating catecholamines 35 and can be potentially arrhythmogenic. 35,36 A recent study of diabetics with autonomic neuropathy showed that apical LV denervation is associated with proximal sympathetic hyperinnervation. 17 This sympathetic dysinnervation pattern could occur in TMR and could further increase the risk of potential lifethreatening arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…It can result in "denervation supersensitivity" to circulating catecholamines 35 and can be potentially arrhythmogenic. 35,36 A recent study of diabetics with autonomic neuropathy showed that apical LV denervation is associated with proximal sympathetic hyperinnervation. 17 This sympathetic dysinnervation pattern could occur in TMR and could further increase the risk of potential lifethreatening arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although the underlying cause of such an increase in heterogeneity of atrial refractoriness is unknown, alterations in sympathetic innervation have been implicated in ventricular arrhythmogenesis by producing spatial heterogeneity of electrophysiology. 10,11 Recently we showed that heterogeneous atrial sympathetic denervation with epicardial phenol increases dispersion of atrial refractoriness and creates a substrate for sustained AF. 12 Whether changes in sympathetic innervation occur during electrophysiological remodeling of the atria and the mechanism by which these changes could alter atrial electrophysiology is unknown.…”
mentioning
confidence: 99%
“…26 In addition, heterogeneity of ventricular repolarization because of heterogeneous sympathetic innervation after MI may have a potential arrhythmogenic effect. [27][28][29] A previous study demonstrated that ventricular arrhythmias occurring in patients who had suffered MI were associated with increased mortality during the follow-up period. 30 In a multicenter study, paired VPCs after MI were associated with a more than 3-fold increase in the odds ratio of mortality compared with those with no VPC, and ventricular tachycardia with a 5-to 6-fold increase in the odds ratio.…”
Section: Effect Of Pc On Ventricular Arrhythmiasmentioning
confidence: 99%